Do sin stocks deprive Islamic stock portfolios of diversification? some insights from the use of MGARCH-DCC - Mustaffa Kamil, Nazrol Kamil; Bacha, Obiyathulla Ismath; Masih, Mansur (2012)
There is argument that Shari’ah compliant portfolios are at a disadvantage in terms of portfolio diversification given that the exclusion of “sin stocks” shrinks the Islamic investor’s investment universe. This paper investigates firstly, whether there is empirical evidence to substantiate such a claim, and secondly, can something be done to alleviate this disadvantage. Our results show that there are statistical evidences that Islamic portfolios are deprived of some benefits of diversification, at the sector level. However, the empirical evidences do not permit us to generalize such a finding at the specific stock level. By analyzing the temporal characteristics of correlations using MGARCH-DCC, we argue that Islamic portfolios can minimize loss of diversification benefit by adopting appropriate portfolio allocation strategies. In particular, market sentiment and commodity prices are two key variables that can drive portfolio allocation switching decisions. In short, while there are some evidences that investors of Shari’ah compliant portfolios are denied of some additional benefits of diversification, there are arguably avenues to mitigate such a disadvantage.